Stock-taking of the Senegal CSAIP: Key Phases, Strategic Approaches, and Groundbreaking Innovations - Ouedraogo, Issa; Siagbe, Golli; Diouf, Latyr; Fatimata, Kone Fatimata; Girvetz, Evan Hartunian (2025)
The Senegal Climate-Smart Agriculture Investment Plan (CSAIP) provides a national framework for mobilizing and coordinating climate-smart agricultural investments. Developed under the leadership of the Ministry of Agriculture, Food Sovereignty and Livestock (MASAE) with support from the Alliance of Bioversity International and CIAT through AICCRA, it integrates scientific evidence, stakeholder participation, and policy alignment with instruments such as the PSE, NAP, and NDC. Structured in seven phases, the CSAIP identifies three flagship programs, sustainable resource management and climate information, resilient livestock and integrated systems, and post-harvest management and market access, with a budget of USD 200 million. Validated technically and politically, and pre-launched at COP29, the CSAIP positions Senegal as a regional leader in climate-resilient, low-carbon agricultural transformation and serves as a model for coordinated investment planning across Africa